Islamic Finance and Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) - Kyriakos-Saad, Nadim (IMF Working Papers; Working Paper ;, 2016)
The money laundering (ML) and terrorist financing (TF) risks associated with conventional finance are generally well identified and understood by the relevant national authorities. There is, however, no common understanding of ML/TF risks associated with Islamic finance. Some are likely to be the same as in conventional finance, but there may also be different risks. This is notably due to: (i) the complexity of some Islamic finance products; and (ii) the nature of the relationship between the institutions and their clients. The limited capacity and experience in the supervision of Islamic finance, especially in jurisdictions that face higher ML/TF risk factors represents an additional vulnerability. The Financial Action Task Force (FATF) standards are implemented without any form of tailoring to the specificities of Islamic finance. The FATF, the Islamic finance standard-setters, and the national regulators should seek a greater understanding of the specific ML/TF risks that may arise in Islamic finance and develop an appropriate response.